2009
DOI: 10.1001/archoto.2009.14
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Combination Anti–Endothelial Growth Factor Receptor and Anti–Vascular Endothelial Growth Factor Receptor 2 Targeted Therapy on Lymph Node Metastasis

Abstract: Objective To evaluate the therapeutic effect of treatment with a combination of the monoclonal antibodies to the VEGFR (DC101) and the EGFR (cetuximab) in an orthotopic nude mouse model of metastatic squamous cell carcinoma of oral tongue (SCCOT). Design In vivo study. Subjects 8- to 12- week-old male athymic nude mice. Intervention To develop orthotopic nude mouse models of SCCOT, OSC-19 cells or luciferase-expressing human OSC-19-luc and JMAR-luc cells were injected into the tongues of nude mice. Anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 27 publications
(35 reference statements)
2
22
0
Order By: Relevance
“…Orthotopic transplantation of tumor cells remains a reproducible and reliable methodology for studying mechanisms and potential therapeutic applications, since phenotypic properties of metastatic cells are governed by the expression of genes that are regulated by interactions with the relevant organ-specific microenvironment [10]. However, these orthotopic OSCC mouse models rely on the use of bioluminescence, which is fraught with transient and variable signals, and they exhibit limited metastasis [11,12] that do not reflect many sites observed in human OSCC [1317]. …”
Section: Introductionmentioning
confidence: 99%
“…Orthotopic transplantation of tumor cells remains a reproducible and reliable methodology for studying mechanisms and potential therapeutic applications, since phenotypic properties of metastatic cells are governed by the expression of genes that are regulated by interactions with the relevant organ-specific microenvironment [10]. However, these orthotopic OSCC mouse models rely on the use of bioluminescence, which is fraught with transient and variable signals, and they exhibit limited metastasis [11,12] that do not reflect many sites observed in human OSCC [1317]. …”
Section: Introductionmentioning
confidence: 99%
“…2,3,11 Recently, a targeted molecular therapy has been reported to greatly improve prognoses of this malignant disease, e.g., Cetuximab, a monoclonal antibody of EGFR. 12,13 However, more potential biological targets for the treatment and therapy of SCCOT need to be explored. Previously, we identified that Kif2a, a microtubule motor protein in the Kinesin-13 family, is involved in the progression, invasion and metastasis of SCCOT.…”
Section: Discussionmentioning
confidence: 99%
“…29 An orthotopic nude mouse model of oral tongue cancer was established by injecting FaDu (2.5 × 10 5 ) or OSC-19 (5 × 10 4 ) cells suspended in 30 µL of serum-free DMEM into the tongues of mice as described previously. 30 …”
Section: Methodsmentioning
confidence: 99%